Comparative Study on LC3-50 with OPC Concrete Using Raw Materials from Pakistan - Muhammad Danyal Sheikh; Tariq Jamil; Tehmina Ayub; Asad-ur-Rehman Khan; Syed Muhammad Bilal; Chuanlin Hu (Advances in Materials Science and Engineering)
The cement industry is expanding rapidly around the globe, despite its significant contribution to global carbon dioxide emissions. Likewise, in Pakistan, the cement industry produces million tons of cement and has a history of contributing as high as 10% of the country’s carbon dioxide emissions annually. The most effective technique for reducing carbon dioxide emissions is to use supplementary cementitious materials (SCMs). Limestone Calcined Clay Cement (LC3-50) is a recently developed cement blend comprised of 50% clinker, 30% calcined clay, 15% raw limestone, and 5% gypsum by weight. The focus of this research is to assess the mechanical properties and durability performance of LC3-50 cement composition formulated using raw materials from Pakistan. The comprehensive case study would help advance the research and commercialization activities in the country. In this study, compressive strength, split tensile, flexural, and pull-out tests were performed for evaluating the mechanical properties. For the assessment of durability, water permeability, sorptivity, carbonation, and rapid chloride penetration test (RCPT) tests were performed as per the available standards. It is concluded that the use of LC3-50 instead of ordinary Portland cement (OPC) improved the strength and durability of the end concrete.